Conductivity studies of starch-based polymer electrolytes - Khiar, A.S.A.; Arof, Abdul Kariem (Springer Verlag (Germany), 2010)
A proton-conducting polymer electrolyte based on starch and ammonium nitrate (NH(4)NO(3)) has been prepared through solution casting method. Ionic conductivity for the system was conducted over a wide range of frequency between 50 Hz and 1 MHz and at temperatures between 303 K and 373 K. Impedance analysis shows that sample with 25 wt.% NH(4)NO(3) has a smaller bulk resistance (R (b)) compared to that of the pure sample. The amount of NH(4)NO(3) was found to influence the proton conduction; the highest obtainable room temperature conductivity was 2.83 x 10(-5) S cm(-1), while at 100 A degrees C, the conductivity in found to be 2.09 x 10(-4) S cm(-1). The dielectric analysis demonstrates a non-Debye behavior. Transport parameters of the samples were calculated using the Rice and Roth model and thus shows that the increase in conductivity is due to the increase in the number of mobile ions.